2018
DOI: 10.3389/fmicb.2018.02709
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Metabolic Regulation to Increase Hfq-Dependent Antibiotic Susceptibility in Pseudomonas aeruginosa

Abstract: The opportunistic human pathogen Pseudomonas aeruginosa is responsible for ~ 10% of hospital-acquired infections worldwide. It is notorious for its high level resistance toward many antibiotics, and the number of multi-drug resistant clinical isolates is steadily increasing. A better understanding of the molecular mechanisms underlying drug resistance is crucial for the development of novel antimicrobials and alternative strategies such as enhanced sensitization of bacteria to antibiotics in use. In P. aerugin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 98 publications
5
31
0
Order By: Relevance
“…Moreover, we have provided evidence for Hfq/Crcmediated regulation of opdP. Hence, the increased susceptibility of P. aeruginosa hfq deletion mutants toward imipenem (Pusic et al, 2018) can be rationalized at the molecular level by these studies. However, we cannot exclude that hitherto unknown Hfq-mediated regulatory circuits additionally impact oprD and opdP regulation.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Moreover, we have provided evidence for Hfq/Crcmediated regulation of opdP. Hence, the increased susceptibility of P. aeruginosa hfq deletion mutants toward imipenem (Pusic et al, 2018) can be rationalized at the molecular level by these studies. However, we cannot exclude that hitherto unknown Hfq-mediated regulatory circuits additionally impact oprD and opdP regulation.…”
Section: Discussionmentioning
confidence: 70%
“…Recent studies revealed that P. aeruginosa hfq deletion mutants showed an increased susceptibility to imipenem (Ducret et al, 2016;Pusic et al, 2018), which coincided with higher oprD and opdP transcript levels in the hfq mutant strain when compared with the parental strain during growth in different media (Supplementary Figure S1 and Supplementary Table S2) (Ducret et al, 2016;Pusic et al, 2018). To verify the impact of Hfq on oprD and opdP translation, oprD::lacZ and opdP::lacZ translational gene fusions were constructed and the β-galactosidase activities conferred by the respective fusion proteins were determined in strains PAO1 and PAO1 hfq harboring plasmids pME6015P tac oprD::lacZ and pME6015P tac opdP::lacZ, respectively.…”
Section: Hfq Is Involved In Translational Regulation Of Oprd and Opdpmentioning
confidence: 99%
See 1 more Smart Citation
“…We predicted that metabolic changes in the membrane transport and metabolism of BCAA and AAA are directly connected to the development of aztreonam resistance. Previous studies have suggested that the carbon catabolite control system CbrAB/Crc regulates BCAA uptake and utilization [51] as well as antibiotic resistance in P. aeruginosa [52][53][54]. Since channels that actively uptake amino acids can also transport antibiotics with sufficient structural similarity (e.g., Escherichia coli glycine transport system can also uptake the antibiotic D-cycloserine [55]), aztreonam resistance can be possibly potentiated by decreasing drug uptake through BCAA transporters via the CbrAB/Crc system, in addition to the efflux provided by the upregulated MexAB-OprM.…”
Section: Discussionmentioning
confidence: 99%
“…Crc represses the translation of lon, thus stabilizing the RhlI and promoting the rhl QS pathway (14). Hfq has also been shown to regulate biofilm formation and contribute to bacterial resistance to gentamicin, fosfomycin, and tetracycline (15,16). Recent studies demonstrated that carbon sources and cellular respiration influence bacterial susceptibility to antibiotics (17,18).…”
mentioning
confidence: 99%